On the path to high-income status or to middle-income trap: The Turkish economy in search of its future - Aysan, Ahmet Faruk; Babacan, Mehmet; Gür, Nurullah; Karahan, Hatice (Palgrave Macmillan, 2018)
The growth episode of the Turkish economy in the 2000s was written based on two integrated fundamentals: fixing the deteriorating dynamics and implementing further reforms to stimulate economic activity. This basic formula led to attractive rates of economic growth, fueled particularly by domestic private investments along with revived consumption and exports. Integrated with the political stability established by single-party governments in the post-2002 period, the improving economic outlook also helped Turkey enjoy record levels of foreign investment, adding momentum to the growth story.
Keywords: Capital Flows; Banking Crisis; Currency Crises